Government Expenditure and Economic Growth: A Cross-Country Analysis - Nhemhafuki, Sanjeev (Journal of Economics Students, 2023)
This paper empirically analyses the relationship between Economic Growth measured in terms of GDP Growth and Government Expenditure, GDP and Population. It employs annual cross-section time series data of the concerned variable of 117 countries from 2001 to 2021. Random Effect model was used for the analysis. The pool-ability of data is tested by the Breusch and Pagan LM test which confirmed that Pooled OLS is not appropriate for the model. The Hausman Specification Test was then conducted for choosing between the Fixed Effect or Random Effect model. The Hausman Specification Test for the Model suggests the Random effect model is appropriate for the analysis of the data. Thus, Random effect regression is used to find the consequences of explanatory and the control variables on the dependent variable. Government Expenditure as an explanatory variable has a positive relationship with the Economic Growth, even in the case of controlling for Population and the Trade Openness. Both the control variable is depicted to have positive relationship with the Economic Growth.